The effect of trade facilitation on sectoral trade - Inmaculada Martínez-Zarzoso; Laura Márquez-Ramos (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2007)
This paper aims to analyse the effect of trade facilitation on sectoral trade flows. We use data from the World Bank's Doing Business Database on the fees associated with completing the procedures to export or import goods in a country, on the number of documents needed and on the required time to complete all the administrative procedures to import and export. An augmented gravity equation is estimated for 13 exporters and 167 importers using a number of estimation techniques, namely OLS, PPML and the Harvey model. A common result is that trade flows increase by lowering transport costs and the number of days required to trade. The outcome supports multilateral initiatives, as that in the WTO, which encourages countries to assess their trade facilitation needs and priorities and to improve them. The measures adopted will not only benefit the country that improves trade facilitation, but also its trading partners.
Keywords: F10; 330; Außenhandelsliberalisierung; Nichttarifäre Handelshemmnisse; Außenhandelsstruktur; Internationale Wirtschaftsbeziehungen; Gravitationsmodell; Transportkosten; Welt